Relationship between limiting factors and Disaster Risk Management in the city of Piura, 2025 - Saavedra Navarro, Carlos Alberto; Zatta Silva, Cesar Augusto; Varillas Trelles, Francisco Javier (LACCEI, 2025)
There is an urgent need to clarify how Disaster Risk Management is implemented, as well as to assess certain conditions that hinder such management and fail to reduce the vulnerability of communities to sudden extreme weather events. The purpose is to determine and evaluate the relationship between limiting factors on disaster risk management in the city of Piura during the year 2025. Through basic research, gathering empirical data and enriching it with scientific evidence, we combine features of descriptive and correlational studies, with observation and analysis as the central technique. To this end, a non-probability sampling was used, selecting professionals with varied experience and administering a questionnaire to 110 engineers associated with the departmental risk management system. Among the findings, specialists agree that these factors exert a direct and significant influence on the development of Disaster Risk Management. Furthermore, all participants point out the lack of a genuine preventive culture, which weakens the organizational structure and the timely reaction capacity of our Disaster Risk Management